Vulnérabilité et résilience des populations riveraines liées à la pollution des eaux lagunaires de la métropole d’Abidjan, Côte d’Ivoire - Koné Brama; Cissé Guéladio; Houenou Pascal Valentin; Obrist Brigit; Wyss Kaspar; Odermatt Peter; Tanner Marcel (VertigO)
The lagoon of Abidjan is polluted by urban waste. The peri urban populations bordering the lagoon are exposed to the pollution.The study aimed at evaluating aspects of vulnerability and resilience of the exposed populations. Nine focus groups discussions were performed in three lagoon-bordering sites. People consider themselves as victims of "the city". Some aspects of vulnerability reported by them among others are that bad smells emanate from the lagoon, flies and mosquitoes coming from lagoon water are responsible for malaria and diarrhea. As aspect of resilience, individual actions of maintaining lagoon banks are undertaken. The social, financial and human capital of the sick persons or their family plays an important role in determining their resilience in the case of disease.